Halal Label, Digital Marketing, and Brand Image: Drivers of Purchasing Decisions in Malang's MSME Food Products - Syaifuddin Fahmi; Peni Indarwati; Muhammad Syarif Hidayatulloh (IQTISHODUNA, 2026)
The aim of this study is to examine how halal labeling, digital marketing, and brand image influence purchasing decisions in the context of packaged food products produced by MSMEs in Malang. A quantitative approach was employed using a survey method, involving 250 respondents who were consumers at retail outlets in Malang and were selected through incidental sampling at the research sites. The analysis was conducted using Structural Equation Modeling (SEM) with the support of the AMOS application to assess the relationships among the variables. The findings indicate that both halal labeling and digital marketing have a positive and significant effect on purchasing decisions. In addition, brand image plays a mediating role in the relationship between halal labeling and digital marketing on purchasing decisions. These results suggest that consumers’ perceptions of halal labeling contribute to strengthening brand image, which in turn enhances their likelihood of making a purchase.  Academically, this study expands the application of consumer behavior theory in the context of halal product marketing, while practically providing guidance for MSMEs to integrate halal labeling and digital marketing strategies in an effort to build a strong brand image. The results of the study fill the existing gap by presenting brand image variables as a mediator.